Kondisi Lingkungan Sosial Budaya Sekolah Dalam Pembentukan Karakter Peserta Didik Di SDN 1 Kadupandak - Warta Warta (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research was motivated by the character building of students at SDN 1 Kadupandak was not optimal. This is related to the socio-cultural environmental conditions of the school. The objectives of this study are: 1) to determine the condition of the socio-cultural environment of the school; 2) obstacles in the socio-cultural environment conditions of the school in the formation of the character of students at SDN 1 Kadupandak; 3) Efforts to overcome obstacles in the socio-cultural environment conditions of the school in building the character of students at SDN 1 Kadupandak. This research uses a qualitative approach with a descriptive method. Research data was obtained from informants, namely principals and teachers. The data collection tools used in this study are interviews, observations, documentation studies, and carrying out triangulation, then the data is processed by data reduction, data presentation, drawing conclusions and verifying data. The results of this study show that the condition of the school's socio-cultural environment in the formation of student character at SDN 1 Kadupandak in terms of routine activities; spontaneous activities; exemplary; and conditioning has been well imolemented. However, there is an aspect that needs to be improved, namely the need for evaluation carried out by teachers related to school culture, because there are still students who need to be guided and reminded by teachers to carry out school culture activities.